The link between human capital and cooperatives performance - Ahmad Shakir, Khairunnisak; Ramli, Azahari; Pulka, Buba Musa; Ghazali, Faizatul Hasliyanti (ProQuest LLC., 2020)
Organisational resources are the fundamental drivers of organisational performance.Human capital is considered one of the organisational resources and many studies had found its positive impact on organisational performance. However, the association between human capital and cooperatives performance is neglected to be studied by previous researchers. The distinct characteristics of cooperatives compared to private or public organisations has paved the way for this paper to investigate the relationship between the human capital of cooperatives board members and cooperatives performance. 1,230 questionnaires were distributed to the randomly selected cooperatives in Peninsular Malaysia and 154 questionnaires were received back from the respondents. 135 questionnaires were usable for the analysis. From the correlation and linear regression analyses, the study discovered that the relationship between the human capital of cooperatives board members and cooperatives performance is positive and significant. These results were supported by findings from previous studies which have been conducted in the non cooperatives sector. Hence, this result allows for the generalisation of the importance of human capital on organisational performance across different types of organisations.